2016
DOI: 10.1371/journal.pone.0166816
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Endotoxin Contamination of Graphene Based Materials Using the TNF-α Expression Test and Guidelines for Endotoxin-Free Graphene Oxide Production

Abstract: Nanomaterials may be contaminated with bacterial endotoxin during production and handling, which may confound toxicological testing of these materials, not least when assessing for immunotoxicity. In the present study, we evaluated the conventional Limulus amebocyte lysate (LAL) assay for endotoxin detection in graphene based material (GBM) samples, including graphene oxide (GO) and few-layered graphene (FLG). Our results showed that some GO samples interfered with various formats of the LAL assay. To overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 31 publications
(33 reference statements)
3
123
0
Order By: Relevance
“…Bare GO complexes siRNA. Endotoxin-free GO sheets were synthesized in house following a modified Hummers method [13][14] (see Experimental). A summary of the physicochemical characterization of the GO dispersion in water, reported elsewhere 15 , is provided in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bare GO complexes siRNA. Endotoxin-free GO sheets were synthesized in house following a modified Hummers method [13][14] (see Experimental). A summary of the physicochemical characterization of the GO dispersion in water, reported elsewhere 15 , is provided in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene oxide (GO). GO was produced in house following the modified Hummer's method as previously described [13][14] . Full characterization of the material has been provided in a previous study 15 where it was termed small GO (s-GO) in order to differentiate it from larger counterparts that have not been used in the present study, and is summarized in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main contamination sources include air, water, glassware and plastic used in the synthesis, and contact with skin (Mukherjee et al 2016). Precursors, intermediates and products may be exposed to these sources of contamination at various steps of the synthesis.…”
Section: Basic Protocol 1: Synthesis and Exfoliation Of Graphene Oxidmentioning
confidence: 99%
“…This range was selected based on previous studies from our laboratory that confirmed lack of toxicity in a number of cell lines (data not shown). Full characterization of the material, produced in house by a modified Hummer's method as previously described (27,28), has been reported in a previous publication (29) and the most relevant parameters are summarized in Table S1. In brief, lateral dimensions did not surpass the 2 μ m threshold and thickness corresponded to 1-2 single GO layers.…”
Section: Rna Samples and Rt-qpcr Reactionsmentioning
confidence: 99%